Creative Commons Public License (CCPL) (Carl Grossmann Verlag, 2025)
Creative Commons licenses have been in use for around 20 years and are established worldwide as a free licensing model. They allow creative people to authorize the general public to use copyrighted materials under certain conditions. This book is the first commentary on the license text of the Creative Commons Public License and thus makes an important contribution to legal practice with Creative Commons licenses. The commentary thus offers the first comprehensive legal analysis of Creative Commons licenses. The handbook section presents specifics for science, public administration and law enforcement, among others.